2018
DOI: 10.1097/jom.0000000000001305
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of a Corporate Culture of Health Assessment Score and Health Care Cost Trend

Abstract: Objective:Employers that strive to create a corporate environment that fosters a culture of health often face challenges when trying to determine the impact of improvements on health care cost trends. This study aims to test the stability of the correlation between health care cost trend and corporate health assessment scores (CHAS) using a culture of health measurement tool.Methods:Correlation analysis of annual health care cost trend and CHAS on a small group of employers using a proprietary CHAS tool.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
11
0
4
Order By: Relevance
“…However, the importance of character strengths and virtues for human flourishing has been long argued by philosophers (Pieper, 1966;Aristotle and Brown, 2009;Baril, 2016) and, more recently, also by psychologists (Graziosi et al, 2020;Niemiec, 2020;Weziak-Bialowolska et al, 2021). Additionally, this study corroborates that, although measures of mental state are covered by instruments of psychological well-being (Ryff and Keyes, 1995) and measures of flourishing are covered by instruments of psychological and social well-being (Diener et al, 2010), a more holistic conceptualization of flourishing goes beyond these areas of human functioning. In particular, this study provides evidence that physical health is just as essential quality for personal well-being as is emotional well-being, confirming theoretical arguments of VanderWeele et al (2019) and prior findings of Weziak-Bialowolska et al (2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the importance of character strengths and virtues for human flourishing has been long argued by philosophers (Pieper, 1966;Aristotle and Brown, 2009;Baril, 2016) and, more recently, also by psychologists (Graziosi et al, 2020;Niemiec, 2020;Weziak-Bialowolska et al, 2021). Additionally, this study corroborates that, although measures of mental state are covered by instruments of psychological well-being (Ryff and Keyes, 1995) and measures of flourishing are covered by instruments of psychological and social well-being (Diener et al, 2010), a more holistic conceptualization of flourishing goes beyond these areas of human functioning. In particular, this study provides evidence that physical health is just as essential quality for personal well-being as is emotional well-being, confirming theoretical arguments of VanderWeele et al (2019) and prior findings of Weziak-Bialowolska et al (2019).…”
Section: Discussionsupporting
confidence: 81%
“…A sense of meaning and/or purpose and other aspects of eudaimonic well-being [i.e., fulfillment of human potential and a meaningful life resulting from self-truth and selfresponsibility (Norton, 1976;Ryan and Deci, 2001)] are also frequently included in composite well-being (flourishing) measures (Ryff and Keyes, 1995;Ryff and Singer, 2008). A comparison of four prominent measures of "flourishing" conducted by Hone et al (2014); for a review of measures of "psychological well-being" and "thriving, " see Su et al (2014), involving the conceptualizations and operationalizations of Keyes (2002Keyes ( , 2007, Diener et al (2010), Huppert and So (2013), and Seligman (2011), revealed that all approaches included items referring to positive relationships, positive affect or engagement, and purpose or meaning (two instruments included both). Three out of four included selfacceptance and/or self-esteem, as well as competence or accomplishment.…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the cost issues, many companies have begun to implement health programs to improve the psycho-physical health of their employees. In particular, studies confirm the usefulness (in certain cases) of health-improving cosmetology programs in the process of forming a corporate culture of health [23]. There are factors that limit the usability of such program.…”
Section: Related Workmentioning
confidence: 88%
“…Current exchangetraded funds (ETFs) that focus on health are those that represent healthcare services, not investment into companies with established cultures of health, distinguished by caring for their workforce's wellbeing in remarkable ways. While there are funds that focus on socially responsible investing (SRI), which may incorporate environmental, social, and governance (ESG) criteria, the focus on the workforce's health and safety is unique [7].…”
Section: Literature Reviewmentioning
confidence: 99%